10y+9-6y+2=

Simple and best practice solution for 10y+9-6y+2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10y+9-6y+2= equation:


Simplifying
10y + 9 + -6y + 2 = 0

Reorder the terms:
9 + 2 + 10y + -6y = 0

Combine like terms: 9 + 2 = 11
11 + 10y + -6y = 0

Combine like terms: 10y + -6y = 4y
11 + 4y = 0

Solving
11 + 4y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 4y = 0 + -11

Combine like terms: 11 + -11 = 0
0 + 4y = 0 + -11
4y = 0 + -11

Combine like terms: 0 + -11 = -11
4y = -11

Divide each side by '4'.
y = -2.75

Simplifying
y = -2.75

See similar equations:

| 4x^2-38x+88=140 | | 5n^2+10n^3= | | 6(3x+5)=5 | | 160q=-q^2+8000 | | 5p^2+10pq^2+pq+2q^3= | | 6(x-8)=2x-20 | | 12a^2+32a+140=0 | | x+x+(x+12)+(x+12)=34 | | x^2+9=04 | | 4m^2+2m-11=0 | | 16m^2+160m+400=8 | | 6k^2-40k-14=0 | | -9u-6=-4(u+4) | | x/2-2x/16=3/6 | | 7+5x=159 | | 8x^2-56x+48=0 | | 0.25x7x(-2)x4x(-1/3)x5x(-0.5)x(-3)x(1/7) | | 0.25x7x(-2)x4x(-1/3)x5x(-0.5)x(-3)X1/7 | | -7(w-3)=-5w+27 | | 3/10=-4/1-1/5 | | 0.14=4/80 | | 1-3x-x^3=2x+1 | | -y=-6x+7 | | 10y+36-38y-47= | | 6.673-(-8.29)=-1.617 | | -6a^7+3a^4-a= | | -20/21*21 | | 17x=0.0005 | | 1/2m=7/8 | | 3.1x^2+x^2=4.9x^2 | | 3t/4-t/3=7-1/6 | | -(5u-v-6)= |

Equations solver categories